On contango, backwardation, and seasonality in index futures - Abd Wahab, Mohd Asraf; Mohamad, Azhar; Sifat, Imtiaz (Inst. Investor Inc., 2019)
The authors investigate contango and backwardation formations and seasonality traits in Malaysia over 22 years spanning 1995 to 2017. Employing graphical observations and statistical tests, contango and backwardation traits appear through market expectations, seasonality, cost of carry model predictions, and index volatility. Unit root, cointegration, and Granger causality tests are employed to assess the existence of long-term relationships between KLCI (cash/spot index) and FKLI (stock index futures) contracts and the direction of the causality relationship. The results are suggestive of cointegration between the futures price index and the spot index in Malaysia. Moreover, a long-run relationship exists between the two variables—a result of backwardation’s predictive ability to find cash market bottoms. Malaysian markets show backwardation in April to June and August, while December is consistently in contango and exhibits moderately high success in the use of a cost-of-carry model in predicting contango and backwardation.